Void-Less Routing Protocol for Position Based Wireless Sensor Network - Joshi , Gyanendra Paeasad (The Graduate School, Ajou University, 2007)
Geographic wireless sensor networks use position information for Greedy routing. Greedy routing works well in dense network whereas in sparse network it may fail and require the use of recovery algorithms because recovery algorithms help the packet to get out of the communication void. However, these algorithms are generally costlier for resource constrained position based wireless sensor type networks. In the present work, we propose a Temporary Ordered Virtual Distance Upgrading (TOVDU) algorithm; a novel idea based on virtual distance upgrading that allows wireless sensor nodes to remove all stuck nodes by transforming the routing graph and forward packet using greedy routing only without recovery algorithm. In TOVDU, the stuck node upgrades distance unless it finds next hop node which is closer to the destination than itself. TOVDU guarantees the packet delivery if there exists a topologically valid path. We use NS-2 to evaluate the performance and correctness of TOVDU and compared the performance with GPSR. Simulation results show that our proposed algorithm generates considerably shorter paths and lower energy consumption.
학위논문(석사)----아주대학교 일반대학원 :전자공학과,2007. 8
Keywords: Position-based wireless sensor network; Greedy routing; Communication Void; Stuck node